Reaksi Harga Saham Terhadap Pengumuman Suspensi dan Pencabutan Suspensi - , Nina Diansari ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this research is to examine the occurrence of positive abnormal returns before the announcement of the suspension and negative abnormal returns after the revocation of the stock suspension and to examine whether there are differences in abnormal returns affected by the suspension of the company stocks before being suspended and after unsuspended. This research uses event study method, which observe abnormal returns and average abnormal returns in period 3 days prior to the announcement of the suspension, the event date, and 3 days after the unsuspension. This research uses secondary data. Tha data is obtained from the Indonesia Stock Exchange and the Capital Market Data Center. The data of this research consist of: daily closing stock price and stock price index. The sample used in this research consists of all stocks listed on the Indonesia Stock Exchange that meet criteria for purposive sampling described. The result shows that: (1) based on the t-test, the Indonesian capital market response on information of the stock suspensionâs announcements and revovation as bad news. This is indicated by the presence of the average abnormal returns are significantly negative after the lifting of the suspension. (2) from the results of paired sample t-test of average abnormal returns, announcements and the lifting of the stock suspension event cause the difference of average abnormal returns statistically before the announcement of the suspension and after revocation of the stock suspension.